The effectiveness of private benefits in fundraising of local charities* - Sieg, Holger (2015)
This paper provides an empirical analysis of the role that private benefits play in explaining charitable donations to large cultural organizations. We develop a multiple discrete choice model with differentiated products. We estimate the model using a unique data set of donor lists for the ten largest cultural and environmental charitable organizations in the Pittsburgh metropolitan area. We find that private benefits that furnish social status to motivate donors to support the related charities.